Heat Treatment of Aluminium Matrix Composite (AMC) Reinforcement Organoclay for Automotive Application - Seputra, Yulius Eka Agung; B, Chanra J. Soegijono. (Jurnal Vokasi Indonesia, 2017)
Aluminum Matrix Composites (AMC) reinforced montmorillonite (MMT) was performed using cationic surfactant , Artificial Aging and stir casting method. The content of MMT as a filler is 3%wt. Characterization were performed using Xray Difractometer, ultrasonic testing, SEM, and Hardness Vickers. The results show increase in crystallographic parameter, decrease in density, shiffting in XRD pattern and increase in hardness.